Nutrition in pregnancy and lactation - García, Marcial (2015)
Pregnancy for the mother's body means overloading their metabolic needs identified by the fetal organogenesis and tissue growth of these organs and extending from the third to ninth month of pregnancy. The problem interferes develop the following facts: the influence of diet during pregnancy on the mother and on the product and the nutritional requirements in pregnancy and lactation.